Jatimulyo GallonCycle Model: A Community Empowerment Approach to Circular Economy and Urban Greening - Helmi Muhammad; Wuli Oktiningrum; Adzimatnur Muslihasari; Eko Yusuf Wahyudi; Niki Puspita Sari (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
Management of household plastic waste in urban areas needs to be directed at source reduction, not just final disposal. In Jatimulyo Village, Malang City, used drinking water gallons have the potential to become a greening medium, but the practice of sorting, reuse, and collective management has not yet been established. This community developed and evaluated the Jatimulyo GallonCycle Model, a community-based circular economy framework integrating waste mapping, circular economy literacy, co-design, technical transformation, and sustainability monitoring to convert used drinking-water gallons into urban greening assets for confined spaces.. Using a Participatory Action Research approach, the activity involved 30 participants from residents, neighborhood associations (RT/RW), the Family Welfare Movement (PKK), youth organizations (karang taruna), and environmental groups through waste mapping, circular economy education, co-design, technical workshops, implementation, evaluation, and reflection. The intervention significantly improved participants' circular economy literacy, with the mean score increasing from 69.22 to 75.09 (an 8.48% improvement; p < .001, Cohen's dz = 1.44). In addition, 50 used drinking-water gallons were transformed into 40 urban greening products installed at 12 community locations, while 86.7% of participants committed to maintaining the products after the program. This study demonstrates a measurable community empowerment model that combines household waste reduction, citizen participation, and urban greening, providing a replicable framework for other urban communities facing similar environmental challenges.